An experimental investigation of age discrimination in the English labor market - Riach, Peter A.; Rich, Judith (Bonn, 2007)
"Carefully-matched pairs of written job applications were made to test for age discrimination in hiring. A twenty-one year-old and a thirty-nine year-old woman applied for jobs where a “new graduate” was sought; men aged twenty-seven and forty-seven, inquired about employment as waiters; women aged twenty-seven and forty-seven, inquired about employment in retail sales. The rate of net discrimination against the older graduate, and against the older waiters in their London inquiries, correspond to the highest rates ever recorded anywhere, by written tests, for racial discrimination. There was a statistically significant preference for the older applicant in retail sales."